Decoding Silkworm Host Plant Interactions: A Comprehensive Review of Chemosensory and Genetic Mechanisms in Bombyx mori and Antheraea assamensis - , Indrani Nath, Pankaj Lushan Dutta, Manasee Hazarika Ahmed (Archives of Current Research International, 2025)
Understanding the intricacies of silkworm–host plant interactions is pivotal for advancing sustainable sericulture and improving silk productivity. This review comprehensively examines the behavioral, chemical, and molecular mechanisms governing host plant recognition and feeding in Bombyx mori (monophagous) and Antheraea assamensis (polyphagous). We detail how silkworm larvae rely on a sophisticated two-step chemosensory process involving maxillary palp and galea, with specialized gustatory receptors responding to stimulants such as chlorogenic acid, β-sitosterol, and sucrose. In B. mori, feeding is highly selective, driven by gustatory and olfactory receptor genes like Gr66, Gr6, and Gr9, which enforce mulberry specificity. Gene-editing studies reveal that these receptors act as molecular gatekeepers of host fidelity. Conversely, A. assamensis exhibits broader chemosensory plasticity, accepting a range of Lauraceae species due to a more diverse receptor repertoire and less stringent phytochemical thresholds. We also explore the role of phytochemicals in muga host plants such as Persea bombycina, and highlight the need for functional genomics studies to decode the sensory basis of polyphagy in non-mulberry silkworms. Insights from this review offer new avenues for artificial diet development, genetic improvement of silkworm strains, and sericultural resource optimization. Furthermore, comparative findings between monophagy and polyphagy contribute to our broader understanding of insect–plant co-evolution and sensory ecology.